Data-Driven Decision-Making: How is data used for decision-making in public schools in Dubai? - Yilmaz, Ozge (2009)
The word data means factual information such as measurements or statistics that are used as a basis for reasoning, discussion, or calculation. Therefore, just as the term implies, data-driven decision making is the process of making data informed decisions. Data is very important in education because statistical data on school programs and student performance provide educators with the only real evidence of the success or failure of educational programs. Data identifies the link between teaching and student performance so that high achievement levels can be obtained (Wade, 2001). This paper seeks to clarify which multiple types of data are being used in the public schools in the Unites Arab Emirates. This paper primarily focuses on the understanding of educators in using multiple types of data in the public schools in the UAE and how much and how well they gather and use data in schools. This paper is divided into three sections. Section 1 describes what data-driven decision making is, including its origins, its implementation in education and an overview of existing literature. Section two draws attention to the answers the research questions by evaluating data-driven decision-making in the two chosen schools. The last section is about recommendations for those schools. This paper addresses four fundamental research questions: • What types of data are administrators and teachers using? • How are administrators and teachers using these data? • What kind of support is available to help with data use? • What factors influence the use of data for decision making?